THE RELATIONSHIP OF NON PERFORMING LOAN (NPL) AND LOAN TO DEPOSIT RATIO (LDR) TO THE ESTABLISHMENT OF RESERVES FOR INCREASED LOSS IN CONVENTIONAL COMMERCIAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE - Andi Hasryningsih Asfar; Alvi Inayati (Yayasan Education and Social Center, 2022)
Banks as intermediary institutions whose operational activities are to collect and distribute funds. In maintaining financial stability in order to remain liquid, banks establish reserves for impairment losses as an effort to anticipate the risk of loss. This study aims to determine the relationship between Non-Performing Loans and Loan to Deposit Ratios to the Establishment of Allowance for Impairment Losses in Conventional Commercial Banks listed on the Stock Exchange. Indonesia for the 2016-2020 period. The method used in this research is the associative method with a quantitative approach. The population in this study are 46 Conventional Commercial Banks. Sampling using purposive sampling technique and selected as many as 6 banking companies. The results of this study indicate that the results of the t-test on Non-Performing Loans on the Establishment of Allowance for Impairment Losses obtained the value of tcount (2.860) > ttable (2.084). The results of the t-test on the Loan to Deposit Ratio variable on the Formation of Allowance for Impairment Losses obtained the value of tcount (-1.284) < ttable (2.084). The results of the F test of Non-Performing Loans and Loan to Deposit Ratio on the Formation of Allowance for Impairment Losses are obtained by the calculated Fvalue (5,224) > Ftable ( 3,35 ). and the Loan to Deposit Ratio has no relation to the Establishment of Allowance for Impairment Losses. Meanwhile, the Non-Performing Loan and the Loan to Deposit Ratio simultaneously have a relationship with the Establishment of Allowance for Impairment Losses